Teacher training in Chile: Where are universities looking? A narrative review - Castillo Paredes, Antonio Jonathan.; Núñez Valdés, Karen Patricia.; Villegas Dianta, Cristian Adrián.; Villena Olivares, Neliot.; López Núñez, Marisol.; Fuentes Rubio, Mario.; Núñez Valdés, Gerson. (MDPI, 2022)
Initial Teacher Training (ITT) has been a recurring theme in recent years in Chilean educational policy and the field of educational research, mainly due to its impact on the Chilean educational system. Under its relevance, this article analyzes ITT and some aspects of its improvement through the revision methodology described by Kart and Kart (2021). Among the main findings, it is possible to mention that the research provides evidence on the decisions that should be made around the teaching profession and the improvement of initial training not only at the institutional level but also at the educational policy level. At the same time, it highlights the need for comprehensive support for future pedagogues and the importance of using the data obtained through the ‘National Diagnostic Evaluation’ for decision making.
Keywords: Diagnostic; University; Evaluación; Profesores; Entrenamiento